Adolescent adaptive behavior profiles in Williams-Beuren syndrome, Down syndrome, and autism spectrum disorder - Carolina Grego Del Cole; Sheila Cavalcante Caetano; Wagner Ribeiro; Arthur Melo E. e. Kümmer; Andrea Parolin Jackowski (BMC, 2017)
Abstract Background Adaptive behavior can be impaired in different neurodevelopmental disorders and may be influenced by confounding factors, such as intelligence quotient (IQ) and socioeconomic classification. Our main objective was to verify whether adaptive behavior profiles differ in three conditions-Williams Beuren syndrome (WBS), Down syndrome (DS), and autism spectrum disorder (ASD), as compared with healthy controls (HC) and with each other. Although the literature points towards each disorder having a characteristic profile, no study has compared profiles to establish the specificity of each one. A secondary objective was to explore potential interactions between the conditions and socioeconomic status, and whether this had any effect on adaptive behavior profiles. Methods One hundred and five adolescents were included in the study. All adolescents underwent the following evaluations: the Vineland Adaptive Behavior Scale (VABS), the Wechsler Intelligence Scale for Children (WISC), and the Brazilian Economic Classification Criteria. Results Our results demonstrated that the WBS group performed better than the DS group in the communication domain, β = −15.08, t(3.45), p = .005, and better than the ASD group in the socialization domain, β = 8.92, t(−2.08), p = .013. The DS group also performed better than the ASD group in socialization, β = 16.98, t(−2.32), p = .024. IQ was an important confounding factor, and socioeconomic status had an important effect on the adaptive behavior of all groups. Conclusions There is a heterogeneity regarding adaptive behavior profiles in WBS, DS, and ASD. These data are important to better design specific strategies related to the health and social care of each particular group.